1995
DOI: 10.1074/jbc.270.51.30765
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of HL-60 Differentiation by a New Class of Retinoids with Selective Activity on Retinoid X Receptor

Abstract: Cellular responsiveness to retinoic acid and its metabolites is conferred through two distinct families of receptors: the retinoic acid receptors (RARs) and the retinoid X receptors (RXRs). Herein, we report on the identification and characterization of several conformationally restricted retinoids, which selectively bind and activate RX receptors. Under the influence of retinoids, HL-60 myelocytic leukemia cells differentiate into granulocytes. This effect is mediated by RAR␣, as has been demonstrated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 39 publications
(31 reference statements)
7
39
2
Order By: Relevance
“…13 However, several studies have shown that in normal RAR␣ protein expressing myeloid cells the synergistic activation of both partners of the RAR-RXR complex is required for activation of RARE transcriptional activity and for many cellular responses, eg induction of cellular differentiation, growth arrest and retinoblastoma protein phosphorylation. 14,15,38 Consistent with these results we show that activation of RAR␣ or RXR alone by synthetic nuclear receptor agonists leads only to a moderate suppression of TF mRNA, TF antigen and TF procoagulant activity in the monoblastic U-937 cells. Full down-regulation was observed when both RAR␣ and RXR were activated.…”
Section: Cd11bsupporting
confidence: 74%
“…13 However, several studies have shown that in normal RAR␣ protein expressing myeloid cells the synergistic activation of both partners of the RAR-RXR complex is required for activation of RARE transcriptional activity and for many cellular responses, eg induction of cellular differentiation, growth arrest and retinoblastoma protein phosphorylation. 14,15,38 Consistent with these results we show that activation of RAR␣ or RXR alone by synthetic nuclear receptor agonists leads only to a moderate suppression of TF mRNA, TF antigen and TF procoagulant activity in the monoblastic U-937 cells. Full down-regulation was observed when both RAR␣ and RXR were activated.…”
Section: Cd11bsupporting
confidence: 74%
“…Since the RXR agonist LG101305 alone had no effect on cell viability, RXR homodimers do not mediate the response. Instead, the fact that the effects of LG101093 and LGD1550 are potentiated by LG101305 supports a model where RAR/RXR heterodimers are optimally activated when both RAR and RXR bind their ligand (Apfel et al, 1995;Minucci et al, 1997). However, RXR activation is clearly not required, since this potentiation by LG101305 was abolished at higher concentrations of LG101093 and LGD1550.…”
Section: Experimental Therapeuticsmentioning
confidence: 76%
“…This is consistent with previous in vitro data, which have indicated that the ligand status of the primary receptor (VDR) can allosterically regulate the response of its RXR partner to 9-cis RA . Such intra-heterodimeric subordination of the RXR AF-2 as a result of allosteric action by the 'primary' partner again mirrors the RXR-RAR heterodimer, where, as discussed above, RXR signaling is inactive unless the RAR partner is liganded, and can only operate through synergy with the RAR ligand (Apfel et al 1995, La Vista-Picard et al 1996, Chiba et al 1997, Minucci et al 1997, Vivat et al 1997. Although synergism by both cognate ligands of the RXR-VDR heterodimer has been reported , Kephart et al 1996, Li et al 1997, we observe no such synergistic activity by 9-cis RA at any concentration in the test systems described in this report.…”
Section: The Role Of 9-cis Ra In the Context Of Rxr-vdr-mediated Signmentioning
confidence: 99%